1998
DOI: 10.1089/thy.1998.8.197
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Thyroiditis as a Favorable Prognostic Factor in Papillary Thyroid Carcinoma

Abstract: Purpose: Assessment of the proliferative ability of cancer cells is necessary not only for the biologic characterization of tumors, but also for the selection of treatment and evaluation of prognosis. Recently, there have been several studies examining the proliferative activity of various malignant tumors using immunohistochemical methods. PCNA is a nuclear protein related to the cell cycle and found with high expression in proliferative tissues, including cancers. Methods: In our study, to evaluate whether P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 17 publications
14
117
3
2
Order By: Relevance
“…Gender The incidence of HT in PTCs according to gender was compared in 23 studies (3,4,5,6,7,14,15,19,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38). HT in PTCs was observed in 1677 of 7346 (23%) female patients and in 180 of 573 (11%) male patients.…”
Section: Clinicopathologic Characteristics Of Ptcs With Htmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender The incidence of HT in PTCs according to gender was compared in 23 studies (3,4,5,6,7,14,15,19,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38). HT in PTCs was observed in 1677 of 7346 (23%) female patients and in 180 of 573 (11%) male patients.…”
Section: Clinicopathologic Characteristics Of Ptcs With Htmentioning
confidence: 99%
“…Survival analysis Four studies including 616 patients of PTC with HT and 4241 of PTC without HT presented recurrence-free survival outcomes (14,28,35,38). The estimated unadjusted HRs ranged from 0.547 to 0.781.…”
Section: Clinicopathologic Characteristics Of Ptcs With Htmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of FNA studies including over 18 000 patients, the prevalence of PTC in HT is estimated to about 1.2% with a non-significant risk ratio (RR) of 0.69. In contrast, prevalence of PTC in HT based on about 10 000 archival thyroid specimens is 27% (RR 1.59; Ott et al 1987, Kashima et al 1998, Loh et al 1999, Kebebew et al 2001, Jankovic et al 2013. Thus, limiting the analysis to archival thyroidectomy specimens might carry a selection bias because the indication for surgery is commonly due to the presence of suspicious nodules.…”
Section: Thyroiditis and Thyroid Cancermentioning
confidence: 99%
“…On the other hand, there is a consensus that peritumeral chronic lymphocytic infiltration alters the clinical presentation of differentiated thyroid cancer. Kebebew and others found that chronic lymphocytes infiltration in patients with PTC correlates with an improved outcome or less aggressive disease (Eisenberg & Hensley 1989, Kashima et al 1998, Kebebew et al 2001.…”
Section: Thyroiditis and Thyroid Cancermentioning
confidence: 99%